Research and Perspectives of New Generation Technological Economic Development Problems on the Industry 4.0 Platform - Alovsat Garaja ALIYEV; Roza Ordukhan SHAHVERDIYEVA (Informatică economică, 2025)
This paper is dedicated to the study of the problems and prospects of new generation technological economic development on the Industry 4.0 platform. The importance of digitization and cyber security in the technological development of the economy was shown, and the relevance of digital transformation, including the application of artificial intelligence, in economic sectors was justified. Based on the analysis of the relevant scientific research works related to the formation and development of the new generation technological economy, its essence, characteristics, scientific-theoretical and methodological bases of its formation were analyzed. Some main characteristics of the transition of economic relations to a new generation at the international level and the National technological grounds of its formation are indicated. Some conceptual approaches and main supporting principles for the formation of the new generation technological economy based on digital transformations have been proposed. The components of the Economy 4.0 platform are systematized. Prospects for the transition to Industry 5.0 in the new generation of technological economic development and prospective research directions for technological innovations within the framework of the Industry 4.0 paradigm have been determined. Relevant recommendations on the application and development prospects of Industry 4.0 platform technologies in the formation and development of the new-generation technological economy were given.